A participação do portador de transtorno mental no contexto familiar - Brischiliari, Adriano (2010)
The general objective of this study was to understand how family members perceive the participation of mental health patients in family life. It is a descriptive study with a qualitative approach using thematic oral history as the data collection technique, carried out between March and May 2010. The contributors were 12 families of mental health patients (MHPs), living in the city of Maringá - PR. Data were analyzed using Bardin's thematic content analysis technique. All ethical aspects were observed and the study was approved under Opinion 509/2009. The study indicates that economic-financial issues are present in the daily lives of MHPs and their family members. When looking for placement in the workforce, MHPs face societal stigma regarding mental illness and the limitations imposed by it. Overcoming these difficulties represents a challenge, requiring attitudes of determination and family support to minimize feelings of uselessness and acquire resilient behaviors, with improved self-esteem and restored citizenship. There are also patients who are not active in the workforce. Some cannot overcome the symptoms of the illness and are unable to perform professionally, whereas others choose not to work, which results in a financial burden on the family. Thus, there are MHPs who work; those who want to work but do not have the opportunity; those who begin to work, but cannot remain active professionally; those who do not want to work; those who receive benefits; those who try, but are unable; those who contribute financially at home; and those who do not. It is observed that the participation of MHPs in the family context and coexistence takes place in different forms. This participation varies from family to family, and happens most effectively in those which allow and encourage the patient's participation, with no apprehension, stigma or prejudice. MHPs can demonstrate their importance in the family and earn their respect and support by performing small family and domestic chores, unburdening the other family members. By experiencing family relations, certain feelings and emotions stand out in the daily routine, resulting especially from the difficulties imposed by the illness. In that sense, it is necessary that family members assist the MHP, while balancing their own needs so that they do not become mentally and physically ill themselves. Families must understand the characteristics of the mental illness so that tribulations and mishaps are not present in these relationships, or at least have less intense effects when they do happen. It is concluded that providing information is an essential condition for definite patient inclusion in the family and all its ramifications. This gap may be filled by nurses, through guidance and follow-up directed at each case, either in specialized mental health services or primary basic health units, at home, in support groups and in associations of family members and patients. This reinforces the need for nurses to be alert to this context, enabling family members and patients so that their relationship is not conflictive and flows naturally.